The Managerial Ability of the Principal in Improving Teacher Motivation and Performance - Safrul, Safrul; Doho, Yohannes Don Bosco; Ghazali, Al; Surur, Miftahus (Budapest International Research and Critics University, 2021)
This study uses a descriptive method with a literature study approach. Collecting data in this study is to use the results of a study of several articles related to the title of this study. The purpose of this literature research is to describe the principal's ability to improve teacher motivation and performance. Managerial principals can increase teacher motivation and performance, when the principal can carry out his three roles, namely, the principal as a leader (leader), the principal as a top manager, and the principal as a supervisor.